Hubungan motivasi kerja dan workplace spirituality dengan counterproductive work behavior pada karyawan perusahaan multimedia - Dwi Pancarani Nur, Mariana; Sari, Erita Yuliasesti Diah (Cognicia, 2024)
This research aims to examine the relationship between work motivation, workplace spirituality, and counterproductive work behavior among employees in a multimedia company. The study utilizes a quantitative approach with a correlational design. Data were collected using the Counterproductive Work Behavior Scale, Work Motivation Scale, and Workplace Spirituality Scale. The sample consisted of 70 employees chosen through saturated sampling techniques. Data analysis was performed using multiple linear regression with IBM SPSS version 23 software. The results of the regression analysis revealed that the F-value for the main hypothesis—examining the relationship between work motivation, workplace spirituality, and counterproductive work behavior—was 19.174, with a significance level of ( p < 0.01 ), indicating a significant relationship. Specifically, work motivation accounted for 12.7% of the variance in counterproductive behavior, while workplace spirituality contributed 23.7%, leading to a total contribution of 36.4%. The remaining 63.6% of the variance is influenced by other variables not discussed in this study. These findings suggest that higher levels of workplace spirituality and work motivation can help reduce counterproductive behavior, foster a positive work environment, and enhance employees' connection to their work.